ANALISIS KEPUASAN PASIEN DI INSTALASI RAWAT INAP RUMAH SAKIT UMUM (RSU) HAJI SURABAYA BERDASARKAN DIMENSI MUTU DABHOLKAR - Kidhung Piranti (The Indonesian Journal of Public Health, 2019)
Community Satisfaction Index (CSI) in Inpatient Installation of Surabaya Hajj Hospital increased during 2012-2016, but it has not reached the standard determined by the hospital, that is 85%. This study aims to analyze the patient satisfaction in the Inpatient Installation of Surabaya Hajj Hospital based on Dabholkar Dimension. This study is descriptive observational analysis by using cross-sectional approach with systematic random sampling technique. The samples obtained  were 142 respondents. This research analyzes patientsatisfaction in the Inpatient Installation by categorizing patient satisfaction in each element based on Dabholkar Dimension. The element with a compositemean ≥ the aggregate of composite average means satisfied and not becoming an issue, while the element with composite mean< the aggregate of composite average means unsatisfied and becomming an issue. Quality service issue can be a problem hence it needs to be resolved as soon as possible. The results of this study can be used to prepare the recommendationof health service improvementto increase patient satisfaction.